2015
DOI: 10.1111/ggi.12606
|View full text |Cite
|
Sign up to set email alerts
|

Impact of potentially inappropriate medication and continuity of care in a sample of Taiwan elderly patients with diabetes mellitus who have also experienced heart failure

Abstract: Among elderly DM patients with HF, COC had positive effects on healthcare outcomes. Improving COC and reducing PIM duration for elderly DM patients with HF seems warranted. Geriatr Gerontol Int 2016; 16: 1117-1126.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 31 publications
0
29
0
Order By: Relevance
“…In Taiwan, a higher percentage of HF patients were having at least one PIM ranging from 81.2% to 89.1% between 2005 and 2010. [ 12 ] However, the interpretation of this high PIM percentage should be done carefully because not all PIMs are recommended to be avoided in this sample, some could be used but with caution. This high consumption of PIMs needs to be controlled by multi‐pronged approaches to limit its long‐term effects on the patient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Taiwan, a higher percentage of HF patients were having at least one PIM ranging from 81.2% to 89.1% between 2005 and 2010. [ 12 ] However, the interpretation of this high PIM percentage should be done carefully because not all PIMs are recommended to be avoided in this sample, some could be used but with caution. This high consumption of PIMs needs to be controlled by multi‐pronged approaches to limit its long‐term effects on the patient.…”
Section: Discussionmentioning
confidence: 99%
“…All patients who attended the outpatient cardiology clinics of a tertiary care center between November 2017 and December 2018 were screened for their eligibility to be included in the study. Since there is no estimate of the percentage of PIMs in elderly HF patients in Lebanon, the percentage was assumed to be 86% based on the findings of Lai et al [ 12 ] who used the same PIM identification criteria. A sample size of 125 was able to estimate the percentage of PIMs with a margin of error of 6% and 95% confidence interval.…”
Section: Methodsmentioning
confidence: 99%
“…PIMs in particular have been associated with adverse events due to drug-disease and drug-drug interactions 6 , and patients with many diseases are generally treated with many prescriptions, which probably include PIMs. Many countries have developed strategies and criteria for identifying and screening PIMs ; however, while one systematic review associated PIMs with readmission 7 , a cohort study on HF patients using the Beers criteria found no such association 8 . Therefore, the role of PIMs in readmissions of HF patients is still controversial.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in the case of diabetes, a higher continuity of medication is able to more successfully reduce the readmission rate, emergency room usage, and medical costs. [2226] In the case of asthma, a higher continuity of outpatient care is able to more effectively decrease next-year emergency room usage in children. [26] Elderly asthmatic patients with a lower continuity of outpatient care have a significantly higher likelihood of having an asthma-related emergency room visit.…”
Section: Discussionmentioning
confidence: 99%